A pilot programme evaluation of social farming horticultural and occupational activities for older people in Italy. (29th August 2018) - Gagliardi, Cristina; Santini, Sara; Piccinini, Flavia; Fabbietti, Paolo; di Rosa, Mirko
Abstract: The aim of this study was to evaluate a 1‐year social farming programme conducted between 2014 and 2015, including horticultural and occupational activities on six agricultural farms for older people in good general health. Social farming is a practice that uses agricultural resources to provide health, social or educational services to vulnerable groups of people. Activity participation, social relationships, physical activity, and the quality of life of the participants were assessed using a pretest, posttest design. A total of 112 subjects were interviewed at baseline, though only 73 participants were retained through the end of the follow‐up, resulting in a dropout rate of 34%. Data analysis revealed significant improvements in both social relationships and overall occupational engagement at the end of the programme, with significant increases in the frequency of contact with friends or relatives as well as the number of activities performed by the participants. This work adds to the literature on the effects of social farming and indicates that farming may provide opportunities for older people to engage in activities that stimulate social behaviours.